Instrumental platform for the static alignment of lower limb prostheses - Chagas, M. P. [UNESP]; Castro, F. R. [UNESP]; Sanches, M. A.A. [UNESP]; Agostinho, J. H.; Alves, C. A. [UNESP]; Carvalho, A. A. [UNESP] (Taylor & Francis, 2020)
The quality of the alignment and adjustment of lower limb prostheses is fundamental in the rehabilitation process, mainly because it contributes to preventing the prostheses from being abandoned. Prosthesis alignment is often performed subjectively based on the experience and knowledge of the healthcare professional. In this work, we present the development of a referenced static alignment equipment for lower limb prostheses. The equipment has an instrumental platform that measures important parameters for suitable alignment of lower limb prostheses, giving the therapist objective data that allow for the best adjustment and alignment of the prosthesis to the individual. The developed system has a novel procedure in the prosthesis adjustment where through a movable base. The prosthesis length can be adjusted with a smooth displacement of 0.35 mm. This minimum displacement is important because the difficulty is greater when the longitudinal adjustment required in the prosthesis is less than 10 mm. The equipment can measure the individual’s center of pressure (COP) in the anteroposterior (AP) and mediolateral (ML) directions, making it possible to adjust the knee and ankle angulation of the prosthesis, and also the alignment in the frontal plane between the healthy and the prosthetic lower limb. The measurement weight accuracy was less than 1%, while the COP measurement accuracies were found to be less than 0.4 cm in both the AP and ML directions. With a sampling frequency of 80 Hz, it is possible to carry out stabilometry analysis and use these data to improve the prosthesis adjustment procedure.
Keywords: Center of pressure; lower limb prostheses; orthopedic device for prosthetic alignment; prostheses static alignment; referenced alignment